Pest categorisation of Helicoverpa zea - EFSA Panel on Plant Health (PLH); Claude Bragard; Katharina Dehnen‐Schmutz; Francesco Di Serio; Paolo Gonthier; Marie‐Agnès Jacques; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2020)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Helicoverpa zea (Lepidoptera: Noctuidae) (American cotton bollworm, corn earworm) for the EU. H. zea is a polyphagous species that feeds on over 100 plant species. The crops most frequently recorded as host plants are maize, sorghum, cotton, beans, peas, chickpeas, tomatoes, aubergines, peppers and, to a lesser extent, clover, okra, cabbages, lettuces, strawberries, tobacco, sunflowers, cucurbits and ornamentals. H. zea preferentially feeds on flowers and fruits of the host. Eggs are laid mostly on maize silks. Larvae feed on the silks and kernels. Pupation takes place in the soil. Hibernation and estivation as pupa are reported. Adults are nocturnal. H. zea is a strong flier, able to fly up to 400 km during migration. Commission Implementing Regulation (EU) 2019/2072 (Annex IIA) regulates H. zea. Fruits and plants for planting, with and without soil, provide potential pathways for entry into the EU. Climatic conditions and the availability of host plants provide conditions to support establishment in the EU. The introduction of H. zea could have an economic impact in the EU through qualitative and quantitative effects on agricultural production (e.g. tomatoes, soybean, sweet corn). Phytosanitary measures are available to reduce the likelihood of entry. H. zea satisfies the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest. H. zea does not meet the criteria of (a) occurring in the EU, and (b) plants for planting being the principal means of spread for it to satisfy the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union regulated non‐quarantine pest.